Law Enforcement Against Violent Crimes By Police Members: A Case Study of the Use Of Excessive Force Against Protesters - Pinayungan Siregar, Pinayungan Siregar; Adi Nur Rohman, Adi Nur Rohman; Sri Wahyuni, Sri Wahyuni (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This research examines law enforcement against acts of violence committed by members of the Indonesian National Police in the context of the use of excessive force when securing demonstrations. The phenomenon is considered a form of violation of criminal law and human rights that has the potential to threaten the principle of the rule of law and undermine the legitimacy of the police institution. The approach used is normative legal research with juridical analysis of the Criminal Code (KUHP), Law No. 2 of 2002 on the Police, Law no. 39 of 1999 on Human Rights, as well as the Chief of Police Regulation relating to the use of force. The results of the study show that although normatively there is an adequate legal basis to limit and regulate the use of force by the apparatus, in practice it often deviates from the principles of legality, proportionality and accountability. Offenders are not always processed through the general criminal mechanism, but only through internal ethical channels, creating an impression of impunity. Therefore, it is necessary to strengthen the criminal accountability system, institutional reform, and independent external oversight so that the principles of the rule of law and the protection of human rights can be thoroughly upheld